2010
DOI: 10.1158/0008-5472.can-10-0511
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Signaling Axis of Matriptase/PDGF-D/β-PDGFR in Human Prostate Cancer

Abstract: Increasing evidence indicates the significance of platelet-derived growth factor receptor-b (b-PDGFR) signaling in prostate cancer (PCa). Accordingly, preclinical studies suggest the potential of b-PDGFR as a therapeutic target in metastatic PCa. However, a ligand responsible for b-PDGFR activation in PCa was unknown, and recent clinical trials with imatinib mesylate showed limited success due to normal tissue toxicity. Similarly, in spite of mounting evidence indicating the significance of matriptase in PCa, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
103
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 47 publications
3
103
0
Order By: Relevance
“…PDGF-A and PDGF-B are secreted in their active form, while secreted PDGF-C and -D polypeptide chains contain a N-terminal CUB (homology to complement components C1r/C1 s, Uegf, Bmp1) domain that needs to be proteolytically removed to enable receptor binding, and are thus produced and released as latent, inactive growth factors (Bergsten et al, 2001;Li et al, 2000;Ustach and Kim, 2005). The activation of PDGF-D is executed by serine proteases, such as urokinase-type plasminogen activator (uPA, also known as PLAU) or matriptase (Ehnman et al, 2009;Ustach et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…PDGF-A and PDGF-B are secreted in their active form, while secreted PDGF-C and -D polypeptide chains contain a N-terminal CUB (homology to complement components C1r/C1 s, Uegf, Bmp1) domain that needs to be proteolytically removed to enable receptor binding, and are thus produced and released as latent, inactive growth factors (Bergsten et al, 2001;Li et al, 2000;Ustach and Kim, 2005). The activation of PDGF-D is executed by serine proteases, such as urokinase-type plasminogen activator (uPA, also known as PLAU) or matriptase (Ehnman et al, 2009;Ustach et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Matriptase knockout mice die shortly after birth due to severe dehydration caused by impaired epidermal barrier function, indicative of a crucial role in development. 2 Among the most recognized matriptase substrates are pro-hepatocyte growth factor, 3 pro-prostasin, 4 protease-activated receptor-2 (PAR-2), 5 pro-urokinase plasminogen activator, 5 CUB domain-containing protein-1, 6 and platelet-derived growth factor-D. 7 Like many other proteases, the inactive zymogen precursor of matriptase needs to be converted to its active form. This is achieved via an initial cleavage occurring at residue Gly 149 , followed by an autoproteolytic cleavage at residue Arg 614 within the RQAR 614 -VVGG sequence of the activation peptide of matriptase.…”
mentioning
confidence: 99%
“…In PCa, ␤-PDGFR is upregulated in ϳ50% of bone metastatic cancer cases and is part of a five-gene signature predicting PCa recurrence postradical prostatectomy (21,36). While the classic ␤-PDGFR ligand PDGF-B has not been often detected in clinical PCa specimens, our group has demonstrated that PDGF-D correlates with PCa Gleason score and tumor stage and induces ␤-PDGFR transformative potential (43). Furthermore, our recent study demonstrated that PDGF-D drives a more invasive program in prostate epithelial cells compared with PDGF-B, supporting the functional significance of the aforementioned clinical and preclinical findings (24).…”
mentioning
confidence: 82%
“…Unlike PDGF-B that is intracellularly processed and secreted as a biologically active dimer, PDGF-D is secreted as a latent dimer containing the NH 2 -terminal CUB domain and the COOH-terminal growth factor domain. The full-length PDGF-D (50 kDa) can be processed into the active 18-kDa growth factor domain and eventually the inactive 15-kDa species by extracellular serine proteases (43). Immunoblot analysis detected full-length PDGF-D in the conditioned media to gradually increase from parental BPH-1 to BPH-1 CAFTD-3 to CAFTD-4 (Fig.…”
Section: Pdgf-d-specific Signaling Supports Extracellular Acidosis Anmentioning
confidence: 95%
See 1 more Smart Citation